[PP.34.01] NECK CIRCUMFERENCE AND WAIST-HIP RATIO, INDEPENDENTLY OF BODY MASS INDEX, ARE MORE RELATED WITH MASKED HYPERTENSION IN OBESE NORMOTENSIVE INDIVIDUALS WITH OBSTRUCTIVE SLEEP APNEA. (September 2016) - Cunha, A.; Gismondi, R.; Correa, C.; Neves, M.; Oigman, W.
Abstract : Objective: Obesity has been associated to development of sleep obstructive apnea (SOA). At same token, SOA is recognized as secondary cause of arterial hypertension (AH). The aim of this study was to evaluate antropometric parameters and ambulatory blood pressure associated to SOA in obese normotensive subjects. Design and method: Obese normotensive (ON) subjects were enrolled in a cross-sectional study. Based on apnea-hypopnea index (AHI) obtained with Watch-PAT200, a home device for sleep study, patients were divided into the group with absent/mild OSA (Group 1, AHI<15) and with moderate/severe OSA (Group 2, AHI > = 15). All patients were submitted to clinical evaluation and 24-h ambulatory blood pressure monitoring with SpaceLabs 90207. Results: We studied 81 ON, 21 men and 61 women, mean age 42 ± 6 yo. ON were divided in 2 groups (G) by apnea-hypopnea index (AHI), G1 <15/h (n = 55) and G2 > = 15/h (n = 26). Anthropometrics data: body mass index (BMI) (G1 = 33.9 ± 3.2 vs G2 = 33.8 ± 2.9 Kg/m 2 p = 0.855), neck circumference (NC) (G1 = 38.0 cm ± 3.3 vs 40.5 ± 3.2 cm p = 0.001) and waist-hip ratio (WHR) (G1 = 0.89 ± 0.01 vs G2 = 0.94 ± 0.01 p = 0.003). Office Systolic (SBP) and Diastolic (DBP) blood pressure were similar (G1 = 121 ± 8 vs G2 = 123 ± 8 mmHg and G1 = 79 ± 8 vs G2 = 77 ± 8 mmHg, p = 0.32). Daytime SBP (G1 = 120 ± 8 vs G2 = 126 ± 6 mmHg, p = 0.037), nighttime SBP (110 ± 10 vs 115 ± 7 mmHg, p = 0.036), daytime DBP (76 ± 7.6 vs 81 ± 8. 5 mmHg p = 0.025) nighttime DBP (66 ± 8 vs 70 ± 7 mmHg p = 0.02) and G2 presented greater nocturne DBP load (45 vs 31%, p = 0.041). In this Obese Normotensive population, AHI presented positive correlation with NC (r = 0.42, p < 0.001) and with WHR (r = 0.44, p < 0.001). Conclusions: In this group of obese normotensive individuals, neck circumference and waist-hip ratio were the factors more associated with the presence of sleep obstructive apnea and masked hypertension, independently of body mass index. These findings suggest that obese normotensive subjects with increased neck circumference should be evaluated with ABPM and sleep study.